Kecemasan Preoperasi pada Pasien Operasi Elektif di Rumah Sakit Al–Fatah dan Rumah Sakit Bhayangkara TK.III Ambon - Stevanie Christalhia; Elpira Asmin; Cokorda Istri Arintha Devi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Mental health is an important aspect of human life that often does not receive as much attention as physical health. One of the mental health problems found in society is anxiety disorders. One of its causes is surgery. Preoperative anxiety is caused by fear of surgical procedures and anesthesia. The purpose of this study was to describe of preoperative anxiety in elective surgery patients at AL-FATAH Hospital and Bhayangkara Hospital TK.III Ambon. This study was a quantitative descriptive study and used a cross-sectional approach, conducted from May to June 2025 with 96 respondents, and used a consecutive sampling technique. The research instrument used the APAIS (Amsterdam Preoperative Anxiety and Information Scale) questionnaire. The showed indicate that most elective surgery patients based on the age group 46-55 years experienced mild anxiety 46.7% (7 people), in the gender group women experienced mild anxiety 40.3% (25 people), in the education level group college education level experienced mild anxiety 50.0% (11 people), in the civil servant occupation group experienced mild anxiety 66.7% (10 people), in the elective surgery type group in general the highest percentage of respondents experienced mild anxiety 34.4% (33 people), in the anesthesia type group regional anesthesia type respondents who experienced mild anxiety were more 35.6% (26 people). Suggestions for hospitals are input for efforts to prevent and reduce the level of anxiety in preoperative patients about anesthesia procedures and surgical procedures. Future researchers is recommended to involve a larger sample size and provide more specific classification of elective surgery types.